Analisis Strategi Bisnis Pada PT Datacomm Diangraha - Enny Noegraheni Hindarwati; Yuniarty Yuniarty; Yasmine Farah (STIE Indonesia Banking School, 2016)
PT Datacomm Diangraha runs in the information technology and communication especially on the system of specializes include network infrastructure, network security, network management, and applications. The purpose of this research to review and analyze the condition of the internal factor and the internal PT Datacomm Diangraha and to determine proper strategy for the company. This research deployed external factor evaluation (EFE), CPM, internal factor evaluation (IFE), grand matrix strategy, internal-external matrix (IE), SPACE matrix, SWOT matrix, and QSPM matrix. According to QSPM matrix, the best strategy for PT Datacomm Diangraha is product development because of the attraction higher than market penetration and market development.